H.I.S Integration With Ecg For Service Acceleration Using Mirth Connect - Ahmad Nur Ihsan Purwanto (International Journal of Education, Information Technology, and Others, 2022)
The integration between H.I.S and the application program of an EKG medical device aims to find a solution in connecting the two different systems using the features of the Mirth Connect software and the international standard HL7 message format. This integration process involves the exchange and transformation of data in every message delivery from the HIS simulation to the tool application and vice versa. Basically, communication software, commonly called bridging software, works to make it easier to send messages to different destination software protocols, and can also easily or (mapping) any destination data to be sent and received by each application. The main key in this bridging software is the mapping that must be configured properly so that message communication can be connected and data can be sent and received according to message requests. For every data transmission, there is a status created and controlled by the program during the process of sending patient data messages, where it is intended as a notification to the user of the state / state that is being run by the program.